SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LOKASI USAHA JASA UMKM MENERAPKAN ANALYTICAL HIERARCHY PROCESS –WEIGHTED PRODUCT METHOD - Diana Diana; Suzy Oktavia Kunang; Iin Seprina (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
This study produces a decision support system for selecting the location of the MSME service business in Alang-Alang Lebar Palembang. There are 2 methods used in this application, namely the Analytical Hierarchy Process (AHP) and the Weighted Product Method (WPM). AHP is used to determine the weight of the criteria and WPM is used to rank the location of the MSME service business. The criteria used in this SPK are rental fees (K1), renovation needs (K2), availability of clean water (K3), availability of electricity supply (K4), presence of asphalt roads (K5), parking space (K6), population density (K7 ), the presence of competitors (K8) and proximity to suppliers (K9). The AHP calculation results show that the rental fee has the highest weight, namely 0.35, which means that the level of importance of the rental fee is 35%. The WPM calculation results show that the location of the 8th MSME service business is the recommended location.